Efektivitas Kompos Tumbuhan Kirinyuh (Chromolaena ordorata L.) untuk Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Anisa, Zea Mutiara; Ananto, Ananto; Sari, Wilna; Putri, Santi Diana (UNIVERSITAS LABUHANBATU, 2024)
Shallots (Allium ascalonicum L.) is a vegetable commodity that is prioritized for development because it has high economic value. Some of the problems that arise in cultivating shallots include the high price of fertilizer and less fertile soil. An alternative to solving these two problems is by using compost. One of the plants that can be used as compost is the kirinyuh plant (Chromolaena odorata L.). Kirinyuh compost can improve soil chemical quality and plant growth and yield. This research aims to determine the dosage of kirinyuh compost for the growth and production of shallot plants. Carried out on the experimental land of the Department of Agroindustry, Padang State University, Sijunjung campus with an altitude of ± 450 meters above sea level, in February-June 2023. The research used a Randomized Block Design with 4 treatments and 6 replications. The levels of treatment given are as follows: K0 Without treatment (control), K1 100 g/polybag, K2 300 g/polybag, K3 600 g/polybag. The parameters observed were plant height (cm), number of leaves (strands), number of bulbs (fruit), wet weight of shallot plants (g). The results of this research had a significant effect on the height of shallot plants with an average height of 39.029 cm (K3), and had no significant effect on other observed parameters. Keywords: kirinyuh, growth, production, shallots